The radiation and energy budget in mesoscale models: an observational study case - Vilà-guerau de Arellano, Jordi; Casso-torralba, Pau (Física de la Tierra, 2008)
The radiation and energy budget modelled by means of the mesoscale model MM5 is evaluated against detail surface and upper-air observations. Three consecutive days (24-26th September 2003) were selected for this study characterized by a weak synoptic forcing and by an optimal development of the diurnal variability of surface and boundary layer variables. Particular emphasis is placed to analyze the sensitivity of these budgets to relevant surface properties like albedo and soil moisture availability. The investigation is extended to determine the sensitivity of the main boundary layer characteristics (boundary layer height and mixed-layer temperature) to variations on surface turbulent fluxes due to different surface conditions